A Rare Case of Chylothorax after Heart Transplantation. (21st October 2019) - Alam, Amit; Hou, Linle; James, Dreamy; Mody, Kanika; Iyer, Deepa; Ghaly, Aziz; Almendral, Jesus
Abstract : Chylothorax is an exceedingly rare but serious complication of orthotopic heart transplantation (OHT). Prompt diagnosis and appropriate management are essential for a good outcome. Management is similar to that of nontransplant patients, but special attention must be given to patients' nutritional and immunological status. Relevant literature on this topic is limited. We describe our experience in the management of chylothorax after OHT and provide a summary of reported cases of this complication after isolated heart and combined heart/lung transplant.